The French Revolution and Napoleon
1 online resource (xxxiv, 304 pages).
Keywords: "This volume collects together a wide selection of primary texts that explain the processes behind the enormous changes undergone by France and Europe between 1787 and 1815, from 'the Terror' to the counter-revolution and from Marie-Antoinette to Bonaparte. The achievements, terror and drama of the French Revolutionary and Napoleonic period restructured politics and society on a grand scale, making this the defining moment for modern European history. While bringing the impact of historical events to life, Philip Dwyer and Peter McPhee provide a clear outline of the period through the selection of key documents, lucid introductory passages and commentary. They illustrate the meaning of the Revolution for peasants, sans-culottes, women and slaves, as well as placing events within a wider European and global context. Students will find this an invaluable source of information on the Revolution as a whole as well as its international significance"--